2015
DOI: 10.1007/s10896-015-9725-7
|View full text |Cite
|
Sign up to set email alerts
|

Decisions to Prosecute Battered Women’s Homicide Cases: An Exploratory Study

Abstract: Discretionary decisions to prosecute cases in which a battered woman kills her partner were investigated using several research strategies and targeting a range of case elements. Law students presented with case elements reported they would consider legal elements over nonlegal (or Bsupplemental^) elements when making a decision to prosecute. In contrast, law students assessed through an open-ended format as to important case factors for deciding to prosecute spontaneously generated high proportions of supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Therefore, as Schuller, Wells, Rzepa, and Klippenstine (2004) suggested, the battered woman who has killed her husband must convince the jury of the "reasonableness" of her lethal action. The amount of violence against the wife before she kills her husband is rather variable, and case law has differed as to whether an objective or subjective interpretation of reasonableness should be applied when juries consider the woman's decision to use force (Follingstad et al, 1989;Follingstad, Rogers, Welling, & Priesmeyer, 2015; Report on Sentencing for Manslaughter in Cases Involving Intimate Relationships, 2003). Another common debate surrounding this involves cases where the woman kills her husband when there is no immediate danger (e.g., while his back is turned or when he is sleeping).…”
Section: Bss In Courtmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, as Schuller, Wells, Rzepa, and Klippenstine (2004) suggested, the battered woman who has killed her husband must convince the jury of the "reasonableness" of her lethal action. The amount of violence against the wife before she kills her husband is rather variable, and case law has differed as to whether an objective or subjective interpretation of reasonableness should be applied when juries consider the woman's decision to use force (Follingstad et al, 1989;Follingstad, Rogers, Welling, & Priesmeyer, 2015; Report on Sentencing for Manslaughter in Cases Involving Intimate Relationships, 2003). Another common debate surrounding this involves cases where the woman kills her husband when there is no immediate danger (e.g., while his back is turned or when he is sleeping).…”
Section: Bss In Courtmentioning
confidence: 99%
“…That being said, these types of strategies are often done in private (vs. getting formal public help; Haselschwerdt et al, 2015) and have been found to be the least successful in actually stopping violence or preventing abuse (Dutton, Goodman, Lennig, Murphy, & Kaltman, 2005;Goodkind, Sullivan, & Bybee, 2004;Riddell, Ford-Gilboe, & Leipert, 2009). Thus, in terms of juror perceptions of BSS, while the woman may be privately resisting the abuse, ultimately, her perceived failure to escape the situation or leave the relationship earlier may influence the jurors' evaluations of the reasonableness of her actions (Follingstad et al, 2015;Schuller & Vidmar, 1992).…”
Section: Perceptions and Attitudes About Bssmentioning
confidence: 99%
“…This limitation makes it necessary to contrast our results with larger samples with a more balanced distribution by sex and academic training in order to achieve more reliable conclusions. It would also be useful to move forward to study the direct impact of gender-victim stereotyping on further actions, for instance by expanding the present design with new questions about decision-making or asking for specific judgments on the target woman, as previous studies did with mock jurors (e.g., Follingstad et al, 2015; Russell & Melillo, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, judicial stereotyping is a common and pernicious barrier to justice, particularly for women victims and survivors of violence (Albertín et al, 2020; Dick, 2020; Fleming & Franklin, 2021; Follingstad et al, 2015; García-Jiménez et al, 2020; Larance et al, 2019; Lelaurain et al, 2018; Masser et al, 2010). Such stereotyping lead legal operators, and judges in particular, to reach a view about these cases based on preconceived beliefs, rather than relevant facts and actual enquiry (Ballesteros Doncel & Blanco Moreno, 2021; Bodelón, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation